2009
DOI: 10.1111/j.1365-2788.2009.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Consensus guidelines into the management of epilepsy in adults with an intellectual disability

Abstract: Background Epilepsy has a pervasive impact on the lives of people with intellectual disability and their carers. The delivery of high-quality care is impacted on by the complexity and diversity of epilepsy in this population. This article presents the results of a consensus clinical guideline process. Results A Delphi process identified a list of priority areas for the development of evidence-based guidelines. All guidelines were graded and consensus on scoring was achieved across the guideline group. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 22 publications
0
76
0
1
Order By: Relevance
“…Therefore, there is a need for measures developed specifically to address the potentially different impact of these medications in patients with ID, given the high level of comorbidities such as Autistic Spectrum Disorder or mental health issues and concomitant medication use, as these are factors which these are factors which also need to be considered within the ID population when examining the side effects of AED medication.With regards to AED side effects in the ID population Kerr (2009) recommended within international consensus guidelines, that baseline cognitive and behavioural assessments should be made and then re-measured after drug changes, with validated measures preferred [3]. There is a lack of established and validated assessment scales for patients with ID and epilepsy, but the fact that this is a heterogenous population and there is a wide range of diversity in communication and cognitive deficits, mean it is challenging to develop a scale or measure that is suitable for all.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a need for measures developed specifically to address the potentially different impact of these medications in patients with ID, given the high level of comorbidities such as Autistic Spectrum Disorder or mental health issues and concomitant medication use, as these are factors which these are factors which also need to be considered within the ID population when examining the side effects of AED medication.With regards to AED side effects in the ID population Kerr (2009) recommended within international consensus guidelines, that baseline cognitive and behavioural assessments should be made and then re-measured after drug changes, with validated measures preferred [3]. There is a lack of established and validated assessment scales for patients with ID and epilepsy, but the fact that this is a heterogenous population and there is a wide range of diversity in communication and cognitive deficits, mean it is challenging to develop a scale or measure that is suitable for all.…”
Section: Resultsmentioning
confidence: 99%
“…As the treatment-emergent adverse events referred to above were reported voluntarily by participants, these may represent side effects that they were particularly Kerr (2009) states that it is important to recognise that the majority of patients in this population are unable to self-report side effects and as such there is a tendency for only the more overt side effects (such as vomiting or weight gain) to come to the attention of the clinician [3]. Our findings suggest that side effects of AEDs are inconsistently and inadequately measured in ID populations, and as such are likely to be under-reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Studies verified that clinicians support the use of decision-making tools and would use them when they are provided. [43] In addition, Ramsay et al [38] suggested that effective management of epilepsy requires a distinctive understanding of the needs of special populations (i.e., ID/DD). Approved plans can reduce the need for rescue medication or emergency services.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to bear in mind that there is no clear evidence that one generation is more or less effective than the other. In the absence of specific treatment guideline, psychotic symptoms in the context of an interictal psychosis (IIP) should be treated in line with wellestablished treatment protocols for primary schizophrenia and related psychoses (56). As already discussed for mood and anxiety disorders, the Commission on Neuropsychiatry of the International League Against Epilepsy published a collection of papers about treatment strategies in adults with epilepsy and psychiatric disorders (19) and one paper was dedicated to the treatment of psychoses (57).…”
Section: Evidence From Rct In Epilepsymentioning
confidence: 99%